Kompensasi, Produktivitas, dan Pengembangan Karir Terhadap Kinerja Karyawan - Peterson Oktorius Sarumaha (IPM2KPE, 2023)
The purpose of this study was to determine the effect of Compensation, Productivity, and Career Development on Employee Performance at PT. Sumber Alfaria Trijaya, Tbk. In processing research data using SPSS 25. The population of this study consisted of 88 employees at PT. Sumber Alfaria Trijaya, Tbk. In this study, quantitative methodology and methods were used to determine non-probability sampling, namely saturated samples. The results showed that the variables Compensation, Productivity and Career Development all have a positive and significant impact on Employee Performance. Simultaneous test results show that Employee Performance is affected in the same way by Compensation, Productivity and Career Development at the same time. Because the R square result for the coefficient of determination test is 0.774, it can be concluded that the Employee Performance variable can be explained by the Compensation, Productivity, and Career Development variables up to the level of 77.4 percent. Keywords: Employee Performance, Compensation, Career Development, Productivity